Vibration Fatigue Life Prediction and Parameter Optimization of Roadheader Picks - He Yang; Li Xiaohuo; Xi Yabing (Jixie chuandong)
In order to determine the vibration fatigue life and influence factors of picks on roadheaders, according to the mechanical model of the picks, the dynamic equation is established, the acceleration response spectrum of the pick is calculated, and the calculated results are used as the vibration excitation to picks. According to the Miner fatigue damage principle and with the help of Workbench, the modal analysis, random vibration analysis and response spectrum analysis of its finite element model are carried out to obtain the stress nephogram of the picks. The stress range of the picks is from 2.713 2×106 Pa to 1.703 5×1010 Pa. The data are imported into the nCode to analyze the vibration fatigue life of picks. The results show that the longest life of the pick is located at the slope area, the second in the arc area, and the lowest in the cylinder area. The corner of the pick is defined as the optimization objective based on particle swarm optimization algorithm, the optimal corner value is obtained, and the life of the picks is increased by an order of magnitude. Finally, through the load sensitivity analysis of the picks, in which the change of the load frequency is an important factor affecting the fatigue life of the picks. The conclusion is important for optimizing the arrangement diagram and improving the life of the picks.